Prácticas de responsabilidad social empresarial de la compañía minera Quiruvilca en el mejoramiento de las condiciones de vida de la comunidad del caserío de Shorey - distrito de Quiruvilca - provincia de Santiago de Chuco - Región La Libertad, año 2015. - Chiguala Rodríguez, Marcela Gelith (2016)
This report, detailed below, is titled "PRACTICES OF CORPORATE SOCIAL RESPONSIBILITY OF MINING COMPANY Quiruvilca ON IMPROVING THE LIVING CONDITIONS OF COMMUNITY CASERÍO Shorey- Quiruvilca district-Santiago de Chuco Province - FREEDOM REGION. 2015, "which shows the result of the activities of Social Responsibility implemented in the village of Shorey by the Mining Company Quiruvilca, taking into account the social, educational and health factors, which were key indicators to know the activities they develop in the community and thus contribute to the satisfaction of needs and development of the community. This, is based on social corporate social responsibility policy, designed for the execution of various activities in the Unit Mining Company Quiruvilca. He also has a source of livelihood surveys and social interviews applied to key stakeholders that are involved, and staff of Human Resources and Social Welfare of the company and external agents, such as institutional leaders and the community are generally. In this sense, it reflects the social commitment of the mining company with the community, meeting the social needs of the village, which are shown in detail from Chapter II of the results and discussions taking so; in the social dimension; the authorization and operation of multiple services unit and the organization and development of staff training workshops and productive enterprise. In the educational dimension; the provision and operation of educational institutions and primary level and granting scholarships and support pre and youth and professional practices in the area. And finally in the health dimension, it has made social responsibility activities as the provision of infrastructure and operation of the medical unit and the development of promotional preventive health campaigns to educate the population. This paper provides information that serves as the basis for a scheme or role model community Corporate Social Responsibility and to improve it in the course of time so it is a precedent to be analyzed at a later regarding the living conditions you have the population of the community Shorey.